Wet coconut fiber as an additive in concrete mixture - Zulfazli, Foazi (2015)
Concrete is one of the materials that is widely used in construction all around the world. This material is used because it has several benefits such as, more durable, energy-efficient, low maintenance, affordability, fire-resistance, excellent thermal mass and also versatility. This study was conducted to determine the workability, compressive strength and flexural strength of concrete to produce good fibrous concrete by using wet coconut fiber as an additive in concrete mixture. Agriculture waste material can help to increase the strength of concrete. The source of natural fiber are found in plant and they are readily environmental friendly and cheap. In addition, natural fiber has an excellent potential to improve the performance of concrete. In this study, workability of concrete means the ability to work with concrete. The workability of the concrete was tested by using slump test.. The slump test was conducted when the concrete mixture still fresh. For compressive strength, the test was conducted to know the strength of cube concrete with different percentages which are 1% and 2% compared between normal concrete. A total of 27 cubes with 150mm×150mm×150mm were used to determine the compressive strength of concrete with addition of wet coconut fiber. For flexural strength, , the test was conducted to know the strength of beam concrete with different percentages with are 1% and 2% compared between normal concrete. A total of 27 beams with 100mm×100mm×500mm were used to determine the strength of concrete with addition of wet coconut fiber All this specimens is curing for 7 days, 14 days and 28 days using water curing method. The best result is from the flexural strength because the concrete with addition of wet coconut fiber was better than normal concrete. The result for 28 days show 9.57 MPa for normal concrete, 9.58 MPa for concrete with 1% addition of wet coconut fiber and 10.95 MPa for concrete with 2% addition of wet coconut fiber